A global pilgrim : the journeys of Pope John Paul II. (Triumph Books, 2005)
From the editors of Chicago Tribune and highlighted by dozens of classic historic photos and populated by unforgettable characters like Lech Walesa and President George H.W. Bush, here is the story of a bold pontiff who towered over his century and then led his church into a new millennium. From his beginnings as a young actor and philosopher from southern Poland, forged in the horrors of World War II, this biography traces how he became a priest, then archbishop of Krakow, and Cardinal before, to the amazement of the world, he became Pope John Paul II, the leader of the world's largest religi.